Perilaku korupsi: Tinjauan psikologi, sosial, politik dan budaya - Eben Ezer Nainggolan (INNER: Journal of Psychological Research, 2024)
Corruption behavior in Indonesia continues to increase from year to year in terms of the quantity or number of people committing corruption and the quality or nominal amount of corruption. Corruption has a severe impact on all aspects of people’s lives. Therefore, research aimed at explaining corruption is needed. The purpose of this study is to provide an explanation of corruption behavior from various disciplines. This research is a literature review study. Research data were collected through search engines such as Google Scholar. Relevant articles were then analyzed using hermeneutics. The findings of this study indicate that many factors can cause corruption, so a multidisciplinary approach is needed. The implications of the research are discussed.